PENGARUH FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MELAKUKAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (STUDI PADA WAJIB PAJAK PBB-P2 KECAMATAN JOMBANG KABUPATEN JOMBANG) - Yusnidar, Johan (Jurnal Mahasiswa Perpajakan, 2015)
This study aimed to clarify the effect of variable SPPT, Knowledge Taxpayer, Quality of Service, Taxpayer Awareness, and Tax PenaltiesÂ  on Taxpayer Compliance. Emperial Studies at Taxpayers Jombang District, Jombang Regency. The method used in this research is explanatory research method, using a questionnaire as data collection tool that is distributed to 116 Taxpayers in Jombang District, Jombang Regency. Statistical method used multiple regression analysis. The result showed that the factors of SPPT, knowledge Taxpayer, Quality of Service, Taxpayer Awareness and Tax Penalties has positive and significant influence both simultaneously and partially. Keyword: SPPT, Knowledge Taxpayer, Quality of Service, Taxpayer Awareness, Tax Penalties, Taxpayer Compliance